Abortifacient effect of decreased decidual and placental galectin-1 expression due to metoclopramide exposure in pregnant rats - Çekmez, Yasemin; Korkmaz, Vakkaş; Çakır, Aslı; Göçmen, Ahmet; Ergün, Yusuf; Gülşen, Serdar (Journal of Reproductive Medicine, Inc., 2017)
OBJECTIVE: To investigate the abortifacient effect of metoclopramide on decidual and trophoblastic tissues with immunohistochemical investigation of galectin-1 expression in pregnant rats. STUDY DESIGN: A total of 24 pregnant rats were selected for the study and divided into 3 groups as untreated, low-dose (1 mg/kg) metoclopramide applied, and high-dose (3 mg/kg) metoclopramide applied from days 5-15 of pregnancy. All rats were laparotomized on day 19 of pregnancy, and number of implantation sites, resorption, and dead or alive fetuses were recorded for evaluating abortifacient activity. Galectin-1 expression was investigated from decidual and trophoblastic tissues via immunohistochemical staining. RESULTS: The mean percentage of abortion was detected higher in the high-dose group than both control and low-dose groups. Galectin-1 staining was more intense and universal in the untreated group than both high- and low-dose metoclopramide exposed groups in labyrinth trophoblasts and decidual tissue. CONCLUSION: Metoclopramide exposure, especially in high doses, may cause abortion, and this drug should be recommended for use during pregnancy only when the benefit outweighs the risk.
Keywords: Abnormalities; Abortifacient Agents; Abortifacients; Abortion; Antiemetics/Adverse Effects; Decidua; Drug-Induced/Epidemiology; Fetal Death/Chemically Induced; Galectin-1; Metoclopramide; Metoclopramide/Adverse Effects; Pregnancy; Teratogens; Trophoblasts